1991
DOI: 10.1177/019459989110500611
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Topical Oral Clindamycin Antibiotic Rinses on the Bacterial Content of Saliva on Healthy Human Subjects

Abstract: The use of systemic antibiotics for major head and neck surgical procedures involving the upper aerodigestive tract is now accepted as an important part of perioperative patient care. Despite knowledge of the high counts of bacteria present in saliva, no preoperative regimen for preparing the mouth has been standardized. Surgical wounds come in contact with saliva during the course of many head and neck procedures. While wound infection rates have been decreased with the use of prophylactic systemic antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The pulmonary literature may provide help as to the best drug and dose. 25 Clindamycin, 67 which is effective against Gram‐positive bacteria and anaerobes, may be an appropriate alternative, especially when combined with topical corticosteroids or alpha‐adrenergic agents. It must be kept in mind that the use of antimicrobials for nasal/sinus irrigation may lead to increased antibacterial resistance and side effects such as hypersensitivity reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary literature may provide help as to the best drug and dose. 25 Clindamycin, 67 which is effective against Gram‐positive bacteria and anaerobes, may be an appropriate alternative, especially when combined with topical corticosteroids or alpha‐adrenergic agents. It must be kept in mind that the use of antimicrobials for nasal/sinus irrigation may lead to increased antibacterial resistance and side effects such as hypersensitivity reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective randomized studies have compared the use of topical antibiotics, such as clindamycin or piperacillin and tozaban, either alone or in combination with systemic prophylaxis. Some preliminary studies have suggested a potential benefit, as they found an objective reduction in bacterial contamination in the intra-operative sites [36,37]. The studies found no statistically significant differences, however, and concluded that their use does not appear to have any benefit in the incidence of postoperative infections [37].…”
Section: The Use Of Topical Antibioticsmentioning
confidence: 99%
“…Frequency of topical antibiotic administration is also important. Elledge et al 10 demonstrated that topical oral clindamycin reduced bacterial counts of oral flora for up to 4 hours, while Grandis et al 11 documented an effect for up to 8 hours. The optimal dosing frequency for sinusitis using topical antibiotics would be best determined scientifically through studies similar to those of Elledge et al 10 and Grandis et al 11 …”
Section: Introductionmentioning
confidence: 99%